Over-expression of Gadd45a enhances radiotherapy efficacy in human Tca8113 cell line - Zhang, Xiao-ying; Qu, Xun; Wang, Cheng-qin; Zhou, Cheng-jun; Liu, Gui-xiang; Wei, Feng-cai; Sun, Shan-zhen (Acta pharmacologica Sinica, 2011)
Aim： To investigate the effect of the growth arrest- and DNA damage-inducible Gadd45a gene on the radiosensitivity of human tongue squamous cell carcinoma cell line to ionizing radiation （IR）. Methods： Short interfering ribonucleic acid （si-RNA） targeting Gadd45a or an irrelevant mRNA （nonsense si-RNA） was chemically synthesized. The constructed si-RNAs were transfected into Tca8113 cells and Gadd45a expression was determined using quantitative real-time PCR and Western-blot. After 24-h exposure to IR at a dose rate of 4 Gy/min, apoptosis of Tca8113 cells was detected using flow cytometry, and radiosensitivity was measured using MTT assays. Results： IR apparently increased the expression of Gadd45a at mRNA and protein levels in Tca8113 cells. The effect was efficiently inhibited by transfection with Gadd45a si-RNA （P〈0.01）. Furthermore, silencing Gadd45a gene significantly increased cell viability and decreased the percentage of apoptotic cells during irradiation, which indicated that IR-induced Gadd45a over-expression could increase the radiosensitivity of Tca8113 cells. Conclusion： These results indicated that targeting Gadd45a may have important therapeutic implications in sensitizing Tca8113 cells tolR.